A carbon / carbon gas guide tube and its preparation method
Patent Information
- Application Number
- CN202511666322.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2045-11-14
AI Technical Summary
[0004]本发明的主要目的在于提供一种碳/碳导气筒及其制备方法,旨在解决现有技术中存在的毛坯材料利用率低下且制备周期较长的问题
1. 与现有的技术方案相比,本发明的技术方案在制备碳/碳导气筒时,不需要添加网胎等原料,且不需要经过针刺等工艺,制备周期小于一个月,周期缩短了2/3;且在芯模外径为碳/碳导气筒内径与预设收缩内径之和的基础上,通过芯模卷制的卷筒坯体的内外径尺寸为净尺寸,使得最终所得碳/碳导气筒的净尺寸与预设的成品导气筒的净尺寸相等,从而减少了在制备过程中的加工次数,显著提高了原料的利用率,并解决了现有技术中存在的毛坯材料利用率低下且制备周期较长的问题。
Smart Images

Figure CN121537219B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of single-crystal silicon furnace technology, and in particular to a carbon / carbon gas guide tube and its preparation method. Background Technology
[0002] Carbon / carbon gas conduit is an important component of the monocrystalline silicon furnace for solar energy. It is used to control the axial temperature gradient of the thermal field and guide the chlorine gas flow, block the thermal radiation from the monocrystalline furnace body and molten silicon to the crystal, facilitate heat dissipation of the crystal, and form the temperature gradient required for crystal growth to improve the crystal growth rate.
[0003] Existing techniques for preparing carbon / carbon gas guide tubes involve first needle-punching a preform of the carbon / carbon gas guide tube onto a mold using a mesh and carbon cloth. This preform is then subjected to gas-phase and liquid-phase densification followed by graphitization. Finally, it is machined to the required dimensions to obtain the carbon / carbon gas guide tube. The problems with this method are low utilization of raw material and a long preparation cycle. Summary of the Invention
[0004] The main objective of this invention is to provide a carbon / carbon gas guide tube and its preparation method, aiming to solve the problems of low utilization rate of raw material and long preparation cycle in the prior art.
[0005] To achieve the above objectives, the present invention provides a method for preparing a carbon / carbon gas guide tube, the method comprising: Carbon fiber cloth is prepared into a prepreg; The prepreg is rolled into a roll blank using a mandrel; The roll blank is subjected to thermosetting treatment, carbonization treatment, graphitization treatment and vapor deposition treatment in sequence to obtain the carbon / carbon gas guide tube; The outer diameter of the core mold is the sum of the inner diameter of the carbon / carbon air guide tube and the preset shrinkage inner diameter.
[0006] Optionally, in the process of preparing carbon fiber cloth into prepreg, the resin used is acetophenolic resin, and the resin content in the prepreg is 40% to 45%.
[0007] Optionally, the temperature of the thermosetting treatment is 160℃~190℃, and the duration is 1h~3h.
[0008] Optionally, the carbonization process includes: Under an inert gas atmosphere, the heat-cured roll blank is subjected to gradient heating using a carbonization treatment device. When the temperature reaches 850℃~950℃, it is held for 2h~4h.
[0009] Optionally, the graphitization process includes: The carbonized roll blank is kept at 1800℃~2000℃ for a preset time, and after the heat preservation is completed, it is cooled in a gradient to complete the graphitization process. The preset duration is determined based on the thickness of the roll blank.
[0010] Optionally, the vapor deposition process includes: Under a preset deposition gas source and a preset deposition temperature, vapor phase deposition is performed on the graphitized roll blank, and the vacuum degree and gas source delivery rate are controlled in stages during the deposition process. The preset deposition gas source is a carbon-containing gas source, and the preset deposition temperature is 1000℃~1200℃.
[0011] Optionally, the gradient heating includes: The carbonization equipment is first heated at 5℃ / min. When the temperature reaches 300℃~350℃, it is held for 0.8h~1.0h. Then, it is heated a second time at 3℃ / min. When the temperature reaches 550℃~600℃, it is held for 1.0h~1.5h. Finally, it is heated to 850℃~950℃ at 2℃ / min.
[0012] Optionally, when the thickness of the rolled blank is ≤10mm, the preset time is 2.0h~2.5h; when the thickness of the rolled blank is 10mm~20mm, the preset time is 3.0h~3.5h; when the thickness of the rolled blank is >20mm, the preset time is 4h. The gradient cooling includes: After the heat preservation is completed, first cool down at a rate of 5℃ / min until the temperature is <1000℃, and then let it cool naturally to room temperature.
[0013] Optionally, the staged control of vacuum level and gas supply volume includes: During the 0h~20h of the vapor deposition process, the preset vacuum degree is 100Pa~800Pa, and pure methane gas is introduced at a rate of 2L / min~3L / min; during the 20h~80h of the vapor deposition process, the vacuum degree is adjusted to 1000Pa~2000Pa, and pure propane gas is introduced at a rate of 3L / min~4L / min; during the 80h~100h of the vapor deposition process, the vacuum degree is adjusted to 500Pa~1000Pa, and propylene gas is introduced at a rate of 2L / min~3L / min.
[0014] To achieve the above objectives, the present invention also provides a carbon / carbon gas guide tube, which is prepared by the above-described preparation method.
[0015] Compared with the prior art, the beneficial effects that the present invention can achieve are as follows: 1. Compared with existing technical solutions, the technical solution of the present invention does not require the addition of raw materials such as mesh blanks when preparing carbon / carbon air guide tubes, and does not require processes such as needle punching. The preparation cycle is less than one month, which is shortened by 2 / 3. Furthermore, based on the fact that the outer diameter of the mandrel is the sum of the inner diameter of the carbon / carbon air guide tube and the preset shrinkage inner diameter, the inner and outer diameters of the rolled blank made by the mandrel are the net dimensions, so that the net dimensions of the final carbon / carbon air guide tube are equal to the preset net dimensions of the finished air guide tube. This reduces the number of processing steps in the preparation process, significantly improves the utilization rate of raw materials, and solves the problems of low utilization rate of raw material and long preparation cycle in the prior art.
[0016] 2. The carbon / carbon air guide tube prepared by the technical solution of the present invention has a carbon fiber content of more than 60%, which can significantly improve the physicochemical and mechanical properties of the air guide tube. Attached Figure Description
[0017] Figure 1 A schematic diagram of the process for preparing a carbon / carbon gas guide tube; Figure 2 A photograph of the carbon / carbon gas delivery tube prepared in Example 1; Figure 3 The image shows the actual carbon / carbon gas guide tube prepared in Example 2 and its dimensional parameters. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] To address the problems of low raw material utilization and long preparation cycle in the existing technology for manufacturing carbon / carbon gas guide tubes, this invention provides a method for manufacturing carbon / carbon gas guide tubes, such as... Figure 1 As shown, the preparation method includes: S10. Prepare carbon fiber cloth into a prepreg; S20. The prepreg is rolled into a roll blank using a mandrel; S30. The roll blank is subjected to thermosetting treatment, carbonization treatment, graphitization treatment and vapor deposition treatment in sequence to obtain the carbon / carbon gas guide tube; The outer diameter of the core mold is the sum of the inner diameter of the carbon / carbon air guide tube and the preset shrinkage inner diameter.
[0020] It should be understood that the aforementioned preset shrinkage inner diameter refers to the size by which the inner diameter of the aforementioned roll blank will shrink after subsequent thermosetting, carbonization, graphitization, and vapor deposition processes, due to factors such as resin decomposition and volatilization, and densification of the carbon matrix structure. This size is a fixed value calculated in advance based on material properties and process parameters.
[0021] Optionally, the material of the aforementioned core mold can be 45# steel or 304 stainless steel.
[0022] Optionally, the aforementioned carbon fiber cloth can be 12K in both warp and weft directions and has an areal density of 400g / m². 2 ~640g / m 2 Plain weave.
[0023] Optionally, the aforementioned carbon fiber cloth can be 6K in both warp and weft directions with an areal density of 280 g / m². 2 ~400 g / m 2 Carbon plain weave fabric.
[0024] It should be understood that the "K" mentioned above is a unit of carbon fiber yarn thickness. 1K represents 1000 carbon fiber monofilaments. For example, 12K means that a bundle of yarn contains 12000 monofilaments. "Warp and weft" refers to the two directions during weaving. For example, a warp and weft of 12K indicates that both the warp and weft yarns of the fabric use 12K carbon fiber, which ensures that the mechanical properties of the fabric are relatively balanced in both directions and avoids the problem of insufficient strength in one direction.
[0025] Optionally, after the prepreg is rolled into a roll blank using a mandrel, a high-temperature resistant OPP (oriented polypropylene) tape can be used to wrap the roll blank to prevent resin overflow during subsequent processing.
[0026] It should be noted that in the above-mentioned method for preparing carbon / carbon gas guide tubes, the design of the outer diameter of the core mold being the sum of the inner diameter of the carbon / carbon gas guide tube and the preset shrinkage inner diameter allows for the shrinkage of the roll blank during carbonization, graphitization, and other processes. This avoids the problem of the finished product's inner diameter being smaller than the design value and ensures that the obtained gas guide tube can be precisely matched with other components in the hot zone of the monocrystalline silicon furnace in specific applications, without the need for subsequent processing corrections, thus reducing processes and costs.
[0027] During the process of rolling prepreg into a roll blank using a mandrel, the prepreg is tightly fitted to the mandrel during molding, and the thickness of the resulting roll blank is the same as the designed thickness of the finished product.
[0028] When determining the amount of prepreg to use, the required length of prepreg can be calculated based on the finished product thickness design, the thickness of a single layer of prepreg, the resin shrinkage rate, and the target thickness of the roll blank.
[0029] In one possible implementation, the resin used in the process of preparing carbon fiber cloth into prepreg is acetophenolic resin, and the resin content in the prepreg is 40% to 45%.
[0030] Optionally, the above-mentioned acetophenolic resin can be a high-residual-carbon acetophenolic resin.
[0031] Optionally, in the method of preparing carbon fiber cloth into prepreg, the carbon fiber cloth can be dried before impregnating it in the resin solution to remove moisture and impurities such as oil from its surface, ensuring that the resin can fully impregnate the fiber monofilaments.
[0032] Optionally, after impregnating the carbon fiber cloth with the resin solution, excess resin can be squeezed out by a pair of precision extrusion rollers, thereby controlling the resin content in the prepreg to be 40%~45%.
[0033] Optionally, after the above impregnation is completed, the prepreg can be dried to achieve semi-curing, in order to prevent solvent evaporation and air bubbles during subsequent tube winding. The semi-cured prepreg is then cut to the required width, and a release film is placed between the layers during winding for later use.
[0034] It should be noted that in the above method of preparing carbon fiber cloth into prepreg, the acetophenolic resin and the resin content of 40% to 45% can ensure that there is enough resin in the unit prepreg to be converted into carbon matrix after carbonization and uniformly wrap the carbon fibers and fill the gaps between the fibers; this can avoid the occurrence of a large number of pores in the components of the air guide tube due to insufficient carbon source.
[0035] After the prepreg is rolled into a roll blank, its resin content is transformed into a carbon matrix after carbonization, which works synergistically with the carbon fibers to form a carbon / carbon composite structure. Simultaneously, the carbon matrix derived from acetal-formaldehyde resin exhibits stronger high-temperature resistance and thermal shock resistance, meeting the high-temperature requirements of the gas guide tube in monocrystalline silicon furnaces without causing structural softening or cracking due to high temperatures. Furthermore, the 40%-45% resin content ensures that the prepreg possesses sufficient viscosity while maintaining a certain degree of flexibility. Combined with the fluidity of acetal-formaldehyde resin, it can fully impregnate the carbon fiber cloth, ensuring uniform prepreg quality.
[0036] In the aforementioned method for preparing carbon fiber cloth into prepreg, if acetaminophen-formaldehyde resin is replaced with ordinary acetaminophen-formaldehyde resin, a large amount of resin will decompose and volatilize during the carbonization process, resulting in a reduction in the remaining carbon matrix. This makes it impossible to fully fill the gaps between the carbon fibers, leading to a significant increase in the porosity of the carbonized roll blank. Increased porosity means that a longer vapor deposition time is required to fill the pores of the blank, which not only increases equipment energy consumption but also prolongs the production cycle. If the vapor deposition time is insufficient, the density and compressive strength of the final carbon / carbon air guide will be significantly reduced. Furthermore, the carbon matrix derived from ordinary acetaminophen-formaldehyde resin has low structural order, and its coefficient of thermal expansion fluctuates greatly during long-term use at high temperatures. This may cause changes in the assembly clearance between the air guide and other components, thereby affecting the control of the thermal gradient.
[0037] If the acetal-phenolic resin mentioned above is replaced with epoxy resin, more than 90% of the resin will decompose and volatilize during the subsequent carbonization process, resulting in a significant reduction in the remaining carbon matrix. This makes it impossible to effectively bond the carbon fibers, potentially causing the carbonized preform to exhibit loose fibers, structural collapse, and even making subsequent graphitization and other processes impossible. Even if graphitization and other processes are completed, the epoxy resin-derived carbon matrix has extremely poor high-temperature resistance. In the high-temperature environment of a single-crystal silicon furnace, it will rapidly oxidize or soften, leading to problems such as cracks, deformation, or failure of the gas guide tube. At the same time, epoxy resin is quite brittle after thermosetting, causing the rolled preform to fracture, and its high shrinkage rate will cause shrinkage cracks in the cured preform.
[0038] In one possible implementation, the temperature of the above-mentioned thermosetting treatment is 160°C to 190°C, for example, 160°C, 170°C, 180°C and 190°C, and the duration is 1h to 3h.
[0039] It should be understood that thermosetting the roll blank allows the phenolic resin in the prepreg to fully cross-link and cure, while also fixing the shape and size of the roll blank.
[0040] It should be noted that when the above-mentioned thermosetting temperature is 160℃~190℃, the resin molecules can undergo a rapid cross-linking reaction, transforming from a linear structure to a three-dimensional network structure. Combined with a curing time of 1h~3h, this ensures high resin curing, transforming the originally soft prepreg roll blank into a solid blank with sufficient strength and rigidity. During the curing process, the temperature of 160℃~190℃ promotes the release of resin volatiles without causing a large outflow of volatiles in a short time due to excessive temperature, thus avoiding the formation of bubbles or cracks inside the blank. The 1h~3h curing time allows the volatiles to be slowly and fully discharged, further reducing the risk of defects forming inside the blank.
[0041] Furthermore, during the aforementioned thermosetting process, if the temperature is below 160°C, the cross-linking reaction of the resin is slow, and the target degree of curing cannot be achieved within the target time. If the temperature is above 190°C, the resin is prone to local overheating, which will cause the surface of the preform to cure prematurely and form a hard shell, preventing the internal volatiles from being discharged and increasing the risk of cracking in the preform.
[0042] In one possible implementation, the carbonization process described above includes: Under an inert gas atmosphere, the heat-cured roll blank is subjected to gradient heating using a carbonization treatment device. When the temperature reaches 850℃~950℃, it is held for 2h~4h.
[0043] In one possible implementation, the gradient heating process in the above carbonization process includes: The carbonization equipment is first heated at 5℃ / min. When the temperature reaches 300℃~350℃, it is held for 0.8h~1.0h. Then, it is heated a second time at 3℃ / min. When the temperature reaches 550℃~600℃, it is held for 1.0h~1.5h. Finally, it is heated to 850℃~950℃ at 2℃ / min.
[0044] Optionally, the carbonization equipment described above can be an inert gas protected high-temperature furnace.
[0045] It should be noted that during the carbonization process described above, the gradient heating and segmented holding methods can be used to gradually release volatile components, thus preventing cracks in the green body. Specifically, during the first heating, when the temperature reaches 300℃~350℃ and is held for 0.8h~1.0h, the resin begins to decompose, releasing low-boiling-point solvents and small molecule impurities. A heating rate of 5℃ / min allows the volatiles to be released slowly and completely, avoiding the problem of bubbles or microcracks inside the green body caused by violent boiling. When heating continues to 550℃~600℃, the resin main chain begins to break, marking the peak period of volatile release. Reducing the heating rate to 3℃ / min and extending the holding time to 1.5h further controls the release rhythm of volatiles, preventing cracking of the green body due to a sudden increase in internal pressure. When the temperature is raised to 850℃~950℃ and held for 2h~4h, the phenolic resin can be completely decomposed into a carbon matrix, maximizing the residual carbon rate. Simultaneously, it avoids excessive carbon matrix ablation due to excessively high temperatures, providing a structurally complete and sufficiently carbon-rich preform for subsequent graphitization, thus ensuring the density and strength of the final carbon / carbon gas guide tube. Furthermore, if the gradient heating is omitted and replaced with a direct heating to around 900℃, it will cause the volatiles to boil violently, resulting in through-cracks in the preform and rendering it unusable.
[0046] In one possible implementation, the above graphitization process includes: The carbonized roll blank is kept at 1800℃~2000℃ for a preset time, and after the heat preservation is completed, it is cooled in a gradient to complete the above graphitization process. The preset duration is determined based on the thickness of the roll blank.
[0047] In one possible implementation, the method for determining the thickness of the roll blank based on a preset duration is as follows: When the thickness of the rolled blank is ≤10mm, heat preservation is required for 2h~2.5h; when the thickness of the rolled blank is 10mm~20mm, heat preservation is required for 3h~3.5h; when the thickness of the rolled blank is >20mm, heat preservation is required for 4h. The gradient cooling includes: After the heat preservation is completed, first cool down at a rate of 5℃ / min until the temperature is <1000℃, and then let it cool naturally to room temperature.
[0048] Optionally, the above-mentioned graphitization treatment equipment can be an induction heating graphitization furnace or a vacuum graphitization furnace.
[0049] It should be noted that during the graphitization process described above, at high temperatures of 1800℃~2000℃, the amorphous disordered layer structure of the carbon fiber cloth gradually transforms into a three-dimensional ordered graphite crystalline structure. This improves the material's electrical and thermal conductivity, reduces resistivity, and enhances thermal conductivity. Simultaneously, the material's thermal shock resistance and chemical stability are also enhanced, and the coefficient of linear expansion decreases, making the material more adaptable to drastic temperature changes and harsh chemical environments. Furthermore, by pre-setting the holding time according to the thickness of the roll blank, it is ensured that blanks of different thicknesses can undergo sufficient graphitization. For thinner blanks, the holding time is relatively shorter to avoid over-processing; while for thicker blanks, extending the holding time allows heat to be fully transferred to the interior, ensuring uniform graphitization throughout the blank and improving product quality stability. During the cooling process, the temperature is first reduced to below 1000℃ at a rate of 5℃ / min, and then allowed to cool naturally to room temperature. This slow cooling method can effectively reduce the thermal stress inside the material, prevent defects such as cracks caused by rapid temperature changes, and help maintain the structural integrity and performance stability of the material.
[0050] During the graphitization process described above, if the temperature is below 1800℃, the graphitization degree of the carbon fiber cloth will be insufficient, failing to fully form an ordered graphite structure. This results in the material's electrical and thermal conductivity, as well as its mechanical properties, failing to meet expectations. If the temperature is above 2000℃, although it may further increase the degree of graphitization, it may also cause excessive grain growth, leading to a decrease in material strength. Furthermore, excessively high temperatures will increase equipment load and energy consumption, raising production costs. During the heat preservation process, if the heat preservation time is too short, the carbon atoms inside the blank cannot fully diffuse and rearrange, and the graphitization reaction will be incomplete, affecting the material's performance. If the heat preservation time is too long, it will not only reduce production efficiency but may also lead to a decline in material performance, such as making the internal structure of the material porous, affecting its strength and density. During the cooling process, if the cooling rate is too fast, large thermal stress will be generated inside the material, potentially causing defects such as cracks or deformation, severely affecting the material's quality and performance. If the cooling rate is too slow, although it can further reduce thermal stress, it will prolong the production cycle and reduce production efficiency.
[0051] In one possible implementation, the above-described vapor deposition process includes: Under a preset deposition gas source and a preset deposition temperature, vapor phase deposition is performed on the graphitized roll blank, and the vacuum degree and gas source delivery rate are controlled in stages during the deposition process. The preset deposition gas source is a carbon-containing gas source, and the preset deposition temperature is 1000℃~1200℃.
[0052] Optionally, the aforementioned carbon-containing gas source can be at least one of methane, propane, and propylene.
[0053] In one possible implementation, the above-mentioned staged control of vacuum level and gas supply volume includes During the 0h~20h of the vapor deposition process, the preset vacuum degree is 100Pa~800Pa, for example, it can be 100 Pa, 200 Pa, 300 Pa, 500 Pa, 600 Pa or 800 Pa, etc., and pure methane gas is introduced at 2L / min~3L / min; during the 20h~80h of the vapor deposition process, the vacuum degree is adjusted to 1000Pa~2000Pa, for example, it can be 1000Pa, 1100 Pa, 1200 Pa, 1500 Pa, 1700 Pa, 1900 Pa or 2000 Pa, etc., and pure propane gas is introduced at 3L / min~4L / min; during the 80h~100h of the vapor deposition process, the vacuum degree is adjusted to 500Pa~1000Pa, for example, it can be 500Pa, 600 Pa, 700 Pa, 800 Pa or 1000 Pa, etc., and pure propylene gas is introduced at 2L / min~3L / min.
[0054] Optionally, the above-mentioned vapor deposition process can be CVD vapor deposition.
[0055] Optionally, the equipment for the above-mentioned vapor deposition process can be a hot-wall chemical vapor deposition furnace, a horizontal or vertical CVD deposition furnace.
[0056] It should be noted that in the above-mentioned vapor deposition process, by controlling the vacuum degree and gas source ratio in stages, the gas guide tube can be efficiently densified and defects reduced. Specifically, within 0h to 20h, a vacuum degree of 100Pa to 800Pa is matched with pure methane gas at a flow rate of 2L / min to 3L / min to ensure that the carbon source concentration in the furnace is low and the diffusion rate is slow. The carbon source can preferentially deposit at the large pores on the surface of the billet, quickly forming a thin and dense outer shell. This can avoid the problem of directly filling the surface with a high concentration of carbon source, which would block the internal pores. Within 20-80 hours, the vacuum level is increased to 1000-2000 Pa, and pure propane gas is supplied at a rate of 3-4 L / min. At a deposition temperature of 1000-1200℃, the propane readily decomposes to generate a large amount of carbon source, accelerating the diffusion rate of the carbon source into the pores inside the billet. After 60 hours, the medium and small pores inside the billet are fully filled, significantly improving the density and strength of the gas guide tube. Within 80-100 hours, the vacuum level is decreased to 500-1000 Pa, and pure propylene gas is supplied at a rate of 2-3 L / min. Propylene decomposition produces a more active carbon source, and the carbon source is more easily enriched on the surface of the gas guide tube under low vacuum. At the same time, it can repair any micro-cracks or depressions that may have occurred on the surface in the first two stages, forming a smoother and denser surface layer, reducing airflow disturbance caused by surface defects during use, and improving its corrosion resistance.
[0057] In the aforementioned vapor deposition process, if the vacuum level is below 100 Pa within 0h to 20h, the gas molecule density inside the furnace is low, and the carbon source diffuses too quickly, easily depositing a thick shell on the surface of the billet. This prevents the internal pores from being filled, resulting in uneven density in the final gas guide tube, which is prone to cracking due to thermal stress at high temperatures. If the vacuum level is above 2000 Pa within 20h to 80h, frequent gas molecule collisions make it difficult for the carbon source to diffuse into the internal pores of the gas guide tube, significantly reducing deposition efficiency. Furthermore, if a mixed gas is used instead of pure methane within 0h to 20h, the carbon source concentration will be too high, causing rapid crusting on the surface of the gas guide tube and blocking the internal pores. If a mixed gas is used instead of pure propane within 20h to 80h, the amount of cracked carbon source will be less, the filling efficiency will be reduced, the internal pores of the gas guide tube will not be fully filled, and the strength will decrease. If other gases are used instead of propylene within 80h to 100h, the activity of the carbon source will be reduced, and the surface defects of the gas guide tube will not be effectively repaired, resulting in poor surface flatness and affecting the temperature gradient control of the hot zone of the single crystal silicon furnace.
[0058] Furthermore, if the temperature is below 1000℃ during the entire deposition process, insufficient carbon source decomposition will result in low carbon source generation and a sharp drop in deposition rate, making it impossible to fill the pores within the target time and reducing the density of the air pump. If the temperature is above 1200℃, the carbon source decomposes too quickly, easily generating disordered carbon that adheres to the pores, leading to poor bonding between the carbon matrix and carbon fibers and a decrease in the mechanical strength of the component.
[0059] It should be noted that in the preparation method of the carbon / carbon air guide tube of the present invention, firstly, the outer diameter of the mandrel is determined based on the shrinkage rate of the roll blank under the set carbonization and graphitization conditions, as well as the inner diameter of the target carbon / carbon air guide tube. The outer diameter of the mandrel, the inner diameter of the carbon / carbon air guide tube, and the preset shrinkage inner diameter are linked to ensure that the inner diameter variation of the final carbon / carbon air guide tube is <0.5mm, the inner diameter meets the standard, and the roundness meets the standard. If the parameters in the carbonization or graphitization process are changed, the resin shrinkage rate will change, resulting in insufficient mandrel allowance and a large deviation in the inner diameter of the finished product. At the same time, the thickness of the carbon / carbon air guide tube is set according to the thermosetting shrinkage rate, thereby determining the thickness of the roll blank, and the amount of prepreg is calculated based on the single-layer thickness of the prepreg. This not only obtains the air guide tube of the target thickness but also significantly improves the raw material utilization rate.
[0060] Secondly, based on a resin content of 40%~45% in the prepreg, parameters for the carbonization process were set. After supplementing the carbon source through vapor deposition, the carbon fiber content of the final carbon / carbon air guide tube was greater than 60%. Furthermore, based on the set carbonization parameters, graphitization methods and parameters were established. Gradient cooling was matched with the gradient heating of the carbonization process; the synergy of both reduced thermal stress through slow temperature control. Simultaneously, based on the graphitization conditions, vapor deposition parameters were determined, ensuring the vapor deposition temperature was lower than the graphitization temperature to avoid damage to the preform structure. If the vapor deposition temperature exceeds 1200℃, it will cause recrystallization of the carbon matrix in the air guide tube, leading to structural deformation.
[0061] As can be seen from the above analysis, in the technical solution of this invention, there is a synergistic effect among the various steps, which together improve the dimensional accuracy, mechanical properties, high-temperature resistance, and production efficiency of the air guide tube product. If the parameters of any step are changed, the performance of the final carbon / carbon air guide tube will decrease.
[0062] To achieve the above objectives, the present invention also provides a carbon / carbon gas guide tube, which is prepared by the above-described preparation method.
[0063] The preparation method described in this invention provides controllable process stability, resulting in carbon / carbon gas guides with strong high-temperature resistance. These guides can operate continuously in environments above 1600℃ without softening or deformation. Compared to traditional graphite gas guides, they exhibit superior thermal shock resistance, capable of handling drastic temperature changes during the opening and closing of monocrystalline silicon furnaces. They also possess corrosion and erosion resistance, resulting in a long service life. Furthermore, they demonstrate excellent density and strength properties, along with good stability.
[0064] Example 1 A method for preparing a carbon / carbon gas guide tube includes the following steps: S10. The carbon fiber cloth is prepared into a prepreg, specifically as follows: High residual carbon aminophenolic resin is added to ethanol and stirred until completely dissolved to form a resin solution with a solid content of 30% to 40%. Then, the solution is filtered to remove impurities and obtain the impregnation solution. The carbon fiber cloth is completely immersed in the impregnation solution for about 5 minutes, then removed and dried to obtain a prepreg with a resin content of 40% to 45%. S20. The prepreg is rolled into a roll blank using a mandrel, specifically as follows: After wiping the surface of the 304 stainless steel mandrel clean, apply a layer of release agent evenly to prevent the blank from sticking to the mandrel and facilitate demolding after curing. Fix the mandrel on the two end chucks of the CNC winding machine, calibrate the coaxiality of the mandrel, and ensure that the mandrel rotates at a uniform speed during winding to avoid the blank from becoming elliptical or having uneven wall thickness. Based on the outer diameter of the mandrel, the preset shrinkage inner diameter, the target wall thickness of the prepreg, the target carbon / carbon air guide inner diameter, and the single-layer thickness of the prepreg, calculate the required cutting width and length of the S10 prepreg. Clamp the cut prepreg onto the unwinding mechanism of the winding machine to ensure that the prepreg is flat and wrinkle-free during unwinding. Start the winding machine, and the prepreg is wound gradually with the rotation of the mandrel. After winding to the target number of layers, use high-temperature OPP tape to wind and fix it at both ends and the middle of the prepreg to obtain the roll prepreg. S30. The rolled blank from S20 is subjected to thermosetting, carbonization, graphitization, and vapor deposition treatments in sequence to obtain the carbon / carbon gas guide tube, as detailed below: Thermosetting treatment: Place the S20 roll blank into the curing oven, close the oven door, and start the ventilation system. First, introduce a small amount of dry air to replace the humid air in the oven and prevent water vapor from condensing on the surface of the blank during the curing process. Then, slowly raise the temperature of the curing oven. When the temperature reaches 160℃, keep it at that temperature for 3 hours. During the heat preservation process, continue to turn on the ventilation to remove the small amount of low-molecular-weight volatiles produced by the resin crosslinking reaction, ensuring that the resin curing degree reaches more than 90%. After the heat preservation is completed, turn off the heating device and then slowly cool it down to room temperature. After cooling is completed, remove the high-temperature OPP tape from the surface of the blank. Carbonization treatment: The thermosetting blank is placed in the carbonization equipment and an inert gas is introduced. Under the inert gas atmosphere, the first heating is carried out at 5℃ / min. When the temperature reaches 300℃, it is held for 1.0h. Then, the second heating is carried out at 3℃ / min. When the temperature reaches 550℃, it is held for 1.5h. Then, the temperature is raised to 850℃ at 2℃ / min and held for 4h. Finally, it is slowly cooled to room temperature. Graphitization treatment: The carbonized billet is placed in a graphitization device and slowly heated in an inert gas atmosphere. When the temperature reaches 1800℃, the holding time is determined according to the thickness of the billet: 2.5h for a thickness ≤10mm; 3.5h for a thickness of 10mm~20mm; and 4h for a thickness >20mm. After holding, a gradient cooling process is started, first cooling at a rate of 5℃ / min to <1000℃, and then allowing it to cool naturally to room temperature. CVD vapor deposition process: The graphitized preform is placed in a vapor deposition apparatus, then a vacuum is drawn and an inert gas is introduced while the temperature is raised. When the temperature reaches 1000℃, the vacuum level and gas supply rate are controlled in stages: from 0h to 20h, the vacuum level is controlled at 100Pa and pure methane gas is introduced at 3L / min; from 20h to 80h, the vacuum level is adjusted to 1000Pa and pure propane gas is introduced at 4L / min; from 80h to 100h, the vacuum level is adjusted to 500Pa and propylene gas is introduced at 3L / min. After completion, the temperature is slowly lowered to room temperature.
[0065] After passing through S10~S30, a carbon / carbon gas guide tube is obtained.
[0066] like Figure 2 The image shown is a physical picture of the carbon / carbon gas guide tube prepared in Example 1.
[0067] Depend on Figure 2 As can be seen, the carbon / carbon air guide tube exhibits the typical appearance of carbon fiber composite materials. The surface shows a clear plain weave texture, indicating that the fibers were arranged regularly and the interlayer bonding was tight during prepreg winding. Furthermore, the cylindrical structure is regular, with flat end faces and no obvious elliptical or uneven wall thickness phenomena, reflecting the precision of the mandrel design and CNC winding process. This ensures the dimensional accuracy of the air guide tube and makes it suitable for assembly requirements in the hot zone of a single-crystal silicon furnace. In addition, observation shows that the surface of the carbon / carbon air guide tube has no obvious pores, cracks, or delamination defects, indicating that the process parameters of thermosetting, carbonization, graphitization, and CVD vapor deposition are well coordinated. Thermosetting ensures full cross-linking of the resin, carbonization ensures a uniform arrangement of the structural sequence, graphitization transforms the carbon matrix into an orderly carbon structure, and CVD vapor deposition effectively fills the pores inside the fibers, ultimately achieving high density and low defect rate in the component. The gas guide tube exhibits a typical black appearance, indicating that the process steps and parameter settings are reasonable, giving the gas guide tube excellent high temperature resistance and chlorine corrosion resistance, which can meet the requirements of long-term high temperature and strong corrosion conditions of single crystal silicon furnace.
[0068] Example 2 In Example 2, S10 to S20 are the same as in Example 1; S30. The rolled blank from S20 is subjected to thermosetting, carbonization, graphitization, and vapor deposition treatments in sequence to obtain the carbon / carbon gas guide tube, as detailed below: Thermosetting treatment: Place the S20 roll blank into the curing oven, close the oven door, and start the ventilation system. First, introduce a small amount of dry air to replace the humid air in the oven and prevent water vapor from condensing on the surface of the blank during the curing process. Then, slowly raise the temperature of the curing oven. When the temperature reaches 190℃, keep it at that temperature for 1 hour. During the heat preservation process, continue to turn on the ventilation to remove the small amount of low-molecular-weight volatiles produced by the resin crosslinking reaction, ensuring that the resin curing degree reaches more than 90%. After the heat preservation is completed, turn off the heating device and then slowly cool it down to room temperature. After cooling is completed, remove the high-temperature OPP tape from the surface of the blank. Carbonization treatment: The thermosetting blank is placed in the carbonization equipment and an inert gas is introduced. Under the inert gas atmosphere, the first heating is carried out at 5℃ / min. When the temperature reaches 350℃, it is held for 0.8h. Then, the second heating is carried out at 3℃ / min. When the temperature reaches 600℃, it is held for 1.0h. Then, the temperature is raised to 950℃ at 2℃ / min and held for 4h. Finally, it is slowly cooled to room temperature. Graphitization treatment: The carbonized billet is placed in a graphitization device and slowly heated in an inert gas atmosphere. When the temperature reaches 2000℃, the holding time is determined according to the thickness of the billet: 2.0h for a thickness ≤10mm; 3.0h for a thickness of 10mm~20mm; and 4h for a thickness >20mm. After holding, a gradient cooling process is started, first at a rate of 5℃ / min to <1000℃, and then naturally cooled to room temperature. CVD vapor deposition process: The graphitized preform is placed in a vapor deposition apparatus, then a vacuum is drawn and an inert gas is introduced while the temperature is raised. When the temperature reaches 1200℃, the vacuum degree and gas source ratio are controlled in stages: from 0h to 15h, the vacuum degree is controlled at 800Pa and pure methane gas is introduced at 8L / min; from 15h to 60h, the vacuum degree is adjusted to 2000Pa and pure propane gas is introduced at 3L / min; from 60h to 80h, the vacuum degree is adjusted to 1000Pa and propylene gas is introduced at 2L / min. After completion, the temperature is slowly lowered to room temperature.
[0069] After passing through S10~S30, a carbon / carbon gas guide tube is obtained.
[0070] A physical image of the carbon / carbon gas delivery tube obtained in Example 2 ( Figure 3 (bottom right corner) and its dimensions as follows Figure 3As shown, this gas guide tube can be applied to electrode sheaths. As can be seen from the figure, the prepared carbon / carbon gas guide tube has an inner diameter of 88mm, an outer diameter of 92mm, and a wall thickness of 2mm. The inner diameter deviation of the finished product is controlled within +1mm, which fully meets the assembly accuracy requirements. Furthermore, the 2mm wall thickness ensures structural strength while avoiding uneven carbonization or graphitization shrinkage caused by excessive wall thickness, demonstrating the synergistic control of process parameters. Simultaneously, the uniform 2mm wall thickness ensures a uniform thermal stress distribution at high temperatures, effectively preventing cracks or deformation caused by uneven wall thickness and ensuring its long-term stability in the hot zone of a single-crystal silicon furnace.
[0071] Comparative Example 1 Comparative Example 1 was set up under Example 2; in Comparative Example 1, the high residual carbon aminophenol resin in S10 was replaced with epoxy resin; other processes and parameters were the same as in Example 2.
[0072] Comparative Example 2 Comparative Example 2 was set up under Example 2. In Comparative Example 2, S10 to S20 were the same as in Example 2. The difference in S30 was that: in the carbonization process, gradient heating was replaced by direct heating to 950°C and then holding for 2 hours; in the graphitization process, the technical solution of pre-setting the graphitization holding time according to the thickness of the roll blank was replaced by holding at 2000°C for 3 hours and then directly cooling to room temperature after holding; in the CVD vapor deposition process, the staged control of vacuum degree and gas source ratio was replaced by introducing a mixed gas of methane and propane at 2000 Pa and holding for 80 hours.
[0073] The carbon / carbon gas guide tube is obtained after passing through S10~S30.
[0074] The performance of the carbon / carbon gas tubes obtained in Examples 1-2 and Comparative Examples 1-2 was measured and analyzed, and the results are shown in Table 1.
[0075] Table 1
[0076] Analysis of the data in Table 1 shows that the carbon / carbon gas guide tubes prepared in Examples 1 and 2 have achieved excellent results in terms of density, compressive strength, bending strength, high temperature resistance, corrosion resistance, dimensional accuracy, and appearance quality, which can meet the assembly requirements. In contrast, the carbon / carbon gas guide obtained in Comparative Example 1 completely failed in performance. This is because, in Comparative Example 1, replacing the high-carbon-residue aminophenolic resin with epoxy resin disrupted the core synergistic effect between the resin and subsequent high-temperature treatment, resulting in a significant decrease in performance. Specifically, using epoxy resin resulted in a carbon residue rate of ≤20%, with over 90% of the resin decomposing into volatiles during carbonization, leading to a severe shortage of carbon source. Consequently, the carbon fibers could not be encapsulated, resulting in a loose fiber structure and high porosity in the prepared prepreg, leading to a significant reduction in strength and density. Secondly, the carbon matrix formed after epoxy resin carbonization is amorphous carbon containing impurities, thus unable to withstand the high-temperature field of a single-crystal silicon furnace above 1000℃. In terms of corrosion resistance, low carbon residue leads to a loose carbon matrix, allowing chlorine gas to easily penetrate and react with the fibers or carbon matrix, and further structural collapse after corrosion, resulting in poor corrosion resistance. In Comparative Example 2, the carbonization process was not graded; instead, the temperature was directly increased, which caused the resin volatiles to boil violently, resulting in through-cracks in the preform. Furthermore, the carbonization was insufficient, and the residual resin decomposed during graphitization, further expanding the pores and reducing density. During graphitization, the holding time was not adjusted according to the thickness, and the direct cooling generated enormous thermal stress, causing cracks on the surface of the gas delivery cylinder and reducing its strength. During CVD vapor deposition, the lack of staged control of vacuum and gas source ratio led to rapid crusting on the surface of the gas delivery cylinder, leaving the internal pores unfilled, increasing porosity, and resulting in insufficient densification. This reduced resistance to chlorine corrosion and made the pores prone to localized wear during airflow scouring.
[0077] Analysis of Examples 1-2 and Comparative Examples 1-2 reveals that in the technical solution of this invention, the selection of acetophenolic resin and the process parameters during subsequent thermosetting, carbonization, and graphitization processes in the preparation of carbon fiber cloth as prepreg produce a synergistic effect, ensuring sufficient carbonization and orderly transformation of the acetophenolic resin with a residual carbon rate ≥50%, providing a carbon matrix preform for subsequent vapor deposition. If this value is replaced with other values, the preform structure will fail. Secondly, during vapor deposition, the staged control of low vacuum and the deposition gas source not only matches the pore distribution of the preform formed by the preceding carbonization and graphitization but also allows for further filling of the preform's interior and surface repair, increasing its density. Furthermore, the outer diameter of the mandrel is the sum of the inner diameter of the carbon / carbon gas guide tube and the preset shrinkage inner diameter, covering the shrinkage dimensions in the thermosetting, carbonization, and graphitization steps. Changes to the preceding steps may lead to increased deviations in the accuracy of the gas guide tube.
[0078] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.
Claims
1. A method for preparing a carbon / carbon gas guide tube, characterized in that, The preparation method includes: Carbon fiber cloth is prepared into a prepreg; The prepreg is rolled into a roll blank using a mandrel; The roll blank is subjected to thermosetting treatment, carbonization treatment, graphitization treatment and vapor deposition treatment in sequence to obtain the carbon / carbon gas guide tube; Wherein, the outer diameter of the core mold is the sum of the inner diameter of the carbon / carbon air guide tube and the preset shrinkage inner diameter; The vapor deposition process includes: performing vapor deposition on the graphitized roll blank under a preset deposition gas source and a preset deposition temperature, and controlling the vacuum level and gas source delivery rate in stages during the deposition process; wherein the preset deposition gas source is a carbon-containing gas source, and the preset deposition temperature is 1000℃~1200℃. The phased control of vacuum degree and gas supply includes: during the 0h~20h of the vapor deposition treatment, the preset vacuum degree is 100Pa~800Pa, and pure methane gas is introduced at a rate of 2L / min~3L / min; during the 20h~80h of the vapor deposition treatment, the vacuum degree is adjusted to 1000Pa~2000Pa, and pure propane gas is introduced at a rate of 3L / min~4L / min; during the 80h~100h of the vapor deposition treatment, the vacuum degree is adjusted to 500Pa~1000Pa, and propylene gas is introduced at a rate of 2L / min~3L / min.
2. The preparation method according to claim 1, characterized in that, In the process of preparing carbon fiber cloth into prepreg, the resin used is acetophenolic resin, and the resin content in the prepreg is 40%~45%.
3. The preparation method according to claim 1, characterized in that, The temperature of the thermosetting treatment is 160℃~190℃, and the duration is 1h~3h.
4. The preparation method according to claim 1, characterized in that, The carbonization process includes: Under an inert gas atmosphere, the heat-cured roll blank is subjected to gradient heating using a carbonization treatment device. When the temperature reaches 850℃~950℃, it is held for 2h~4h.
5. The preparation method according to claim 1, characterized in that, The graphitization process includes: The carbonized roll blank is kept at 1800℃~2000℃ for a preset time, and after the heat preservation is completed, it is cooled in a gradient to complete the graphitization process. The preset duration is determined based on the thickness of the roll blank.
6. The preparation method according to claim 4, characterized in that, The gradient heating temperature rise includes: The carbonization equipment is first heated at 5℃ / min. When the temperature reaches 300℃~350℃, it is held for 0.8h~1.0h. Then, it is heated a second time at 3℃ / min. When the temperature reaches 550℃~600℃, it is held for 1.0h~1.5h. Finally, it is heated to 850℃~950℃ at 2℃ / min.
7. The preparation method according to claim 5, characterized in that, When the thickness of the rolled blank is ≤10mm, the preset time is 2.0h~2.5h; when the thickness of the rolled blank is 10mm~20mm, the preset time is 3.0h~3.5h. When the thickness of the roll blank is >20mm, the preset duration is 4h; The gradient cooling includes: After the heat preservation is completed, first cool down at a rate of 5℃ / min until the temperature is <1000℃, and then let it cool naturally to room temperature.
8. A carbon / carbon gas guide tube, characterized in that, The carbon / carbon air guide tube is prepared by the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
A carbon-carbon guide tube and preparation method thereof
CN119751108A